Recent Development of Nickel-Based Electrocatalysts for Urea Electrolysis in Alkaline Solution - Anuratha, Krishnan; Rinawati, Mia; Wu, Tzu-Ho; Yeh, Min-Hsin; Lin, Jeng-Yu (Nanomaterials (Basel, Switzerland), 2022)
Recently, urea electrolysis has been regarded as an up-and-coming pathway for the sustainability of hydrogen fuel production according to its far lower theoretical and thermodynamic electrolytic cell potential (0.37 V) compared to water electrolysis (1.23 V) and rectification of urea-rich wastewater pollution. The new era of the “hydrogen energy economy” involving urea electrolysis can efficiently promote the development of a low-carbon future. In recent decades, numerous inexpensive and fruitful nickel-based materials (metallic Ni, Ni-alloys, oxides/hydroxides, chalcogenides, nitrides and phosphides) have been explored as potential energy saving monofunctional and bifunctional electrocatalysts for urea electrolysis in alkaline solution. In this review, we start with a discussion about the basics and fundamentals of urea electrolysis, including the urea oxidation reaction (UOR) and the hydrogen evolution reaction (HER), and then discuss the strategies for designing electrocatalysts for the UOR, HER and both reactions (bifunctional). Next, the catalytic performance, mechanisms and factors including morphology, composition and electrode/electrolyte kinetics for the ameliorated and diminished activity of the various aforementioned nickel-based electrocatalysts for urea electrolysis, including monofunctional (UOR or HER) and bifunctional (UOR and HER) types, are summarized. Lastly, the features of persisting challenges, future prospects and expectations of unravelling the bifunctional electrocatalysts for urea-based energy conversion technologies, including urea electrolysis, urea fuel cells and photoelectrochemical urea splitting, are illuminated.